Draft Genome Sequence of a New Fusarium Isolate Belonging to Fusarium tricinctum Species Complex Collected From Hazelnut in Central Italy - Turco, Silvia; Grottoli, Alessandro; Drais, Mounira Inas; De Spirito, Carlo; Faino, Luigi; Reverberi, Massimo; Cristofori, Valerio; Mazzaglia, Angelo (Frontiers in Plant Science, 2021)
In summer 2019, during a survey on the health status of a hazelnut orchard located in the Tuscia area (the province of Viterbo, Latium, Italy), nuts showing symptoms, such as brown-grayish spots at the bottom of the nuts progressing upward to the apex, and necrotic patches on the bracts and, sometimes, on the petioles, were found and collected for further studies. This syndrome is associated with the nut gray necrosis (NGN), whose main causal agent is Fusarium lateritium. Aiming to increase knowledge about this fungal pathogen, the whole-genome sequencing of a strain isolated from symptomatic hazelnut was performed using long Nanopore reads technology in combination with the higher precision of the Illumina reads, generating a high-quality genome assembly. The following phylogenetic and comparative genomics analysis suggested that this isolate is caused by the F. tricinctum species complex rather than F. lateritium one, as initially hypothesized. Thus, this study demonstrates that different Fusarium species can infect Corylus avellana producing the same symptomatology. In addition, it sheds light onto the genetic features of the pathogen in subject, clarifying facets about its biology, epidemiology, infection mechanisms, and host spectrum, with the future objective to develop specific and efficient control strategies.